2021
DOI: 10.3389/fspor.2021.778813
|View full text |Cite
|
Sign up to set email alerts
|

Contextual Variables Affect Running Performance in Professional Soccer Players: A Brief Report

Abstract: This study aimed to investigate the effects of contextual variables on running performance in Brazilian professional soccer players. Twenty male players from one club participating in the 1st Division of the Brazilian soccer championship were analyzed during 35 matches. Global Positioning System was used to determine total distance (TD) covered, distance covered and actions in high intensity and sprinting, and the number of accelerations, and decelerations. The independent variables used were match location, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 32 publications
3
23
0
Order By: Relevance
“…Despite the interesting findings of the current study, some limitations should be acknowledged. Firstly, our study only focused on one elite European professional soccer team across a 6-week period, and as a result, the findings and practical implications must be considered with caution when applying to another set of players from a league with different characteristics such as match demands, travel [ 48 ], climate [ 49 ], and over an extended period of time during a different phase of the season (early-, mid-, late-season, congested Christmas schedule). Furthermore, the sample size was also a limitation due to this study being conducted in the real-world, conducted with players from an elite soccer club.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the interesting findings of the current study, some limitations should be acknowledged. Firstly, our study only focused on one elite European professional soccer team across a 6-week period, and as a result, the findings and practical implications must be considered with caution when applying to another set of players from a league with different characteristics such as match demands, travel [ 48 ], climate [ 49 ], and over an extended period of time during a different phase of the season (early-, mid-, late-season, congested Christmas schedule). Furthermore, the sample size was also a limitation due to this study being conducted in the real-world, conducted with players from an elite soccer club.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that such contextual variables as game location 34 , match outcome 35 or opponent level 36 could affect the physical match performance. A recent study of Augusto et al 37 considered the coach turnover as another potential contextual variable. In this research the analysis of a single team indicated that coach replacement negatively affect the match high-intensity activities.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, contextual variables can influence several match outcomes (Aquino et al, 2020;Augusto et al, 2021;Gonçalves et al, 2021). For example, total distance and high-intensity running in home matches were higher than in away matches (Aquino et al, 2020).…”
Section: Introductionmentioning
confidence: 99%